The role of quality technical education for technological advancement in Nigeria: The interface - Akegbejo, David Adeleke (Yayasan Mitra Persada Nusantara, 2024)
This paper examines the interface between quality technical education and technological advancement. The purpose of this study is to evaluate the quality of education provided as regard technical education in relationship to technological advancement in Nigeria. The research design adopted for the study was a survey. The study was carried out in three public technical colleges in Ondo State. The population of the study comprised all students and staff of the three government technical colleges in Ondo State. There was no sample in the study. Two instruments were used for data collection. The instrument for data collection was a self-structured questionnaire. Drafted copies of the questionnaire with a total of forty items were validated by three experts, and one specialized in Measurement and Evaluation. The test-retest method was used to ascertain the reliability of the instruments. The instrument was subjected to a reliability test using an estimate of internal consistency developed by Pearson Product Moment Correlation (PPMC). The overall reliability index for the instrument was 0.88 and therefore deemed reliable. 103 copies of the questionnaire were administered to the respondents by the researcher and with three research assistants. Percentage, mean and standard deviation were used to answer research questions. For decision to be reached regarding the mean, the upper and lower limits of the mean were adopted. Finding showed that lack of qualitative technical education hampered the technological advancement and deprived Nigeria from joining the league of developed nations because quantity is replacing quality. Therefore the following recommendation were made; the federal government and state should consider siting technical colleges in each local government areas just as it has unity colleges and higher institutions across the states that will serve as models in times of quality; emphasis must be placed on skills acquisition and technological advancement at all levels of our technical education to produced graduates that do not just have the certificates but skills; funding of technical schools should meet up to UNESCO recommendation of 26%.